2003
DOI: 10.1046/j.1365-2311.2003.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of caterpillar performance and the suitability of two host plant species

Abstract: Abstract. 1. The butterfly Melitaea cinxia uses two host plant species in the A Ê land Islands of south-west Finland. Survey data show that host plant use is spatially variable and that the two species are not used (fed on by M. cinxia larvae) in proportion to their abundances. The pattern of host plant use by M. cinxia has been attributed in part to plant distribution and spatial variation of butterfly oviposition preference.2. The additional roles that may be played by spatial variation in host plant quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 37 publications
4
45
0
2
Order By: Relevance
“…This is on par with the natural rate of overwintering survival (van Nouhuys et al, 2003). Their probability of survival was significantly lower when they originated from plant genotypes with high levels of catalpol before diapause (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…This is on par with the natural rate of overwintering survival (van Nouhuys et al, 2003). Their probability of survival was significantly lower when they originated from plant genotypes with high levels of catalpol before diapause (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…However, no preference and performance studies involving these hosts have been performed on this butterfly subspecies living in tropical areas. As mentioned above, a number of studies have been performed on butterflies (Singer 1972;van Nouhuys et al 2003), moths (Jallow and Zalucki 2003;Liu et al 2010), beetles (Yamaga and Ohgushi 1999), flies (Rattanapun et al 2010), spittlebugs (Craig and Ohgushi 2002) and other insects to test the performance-preference hypothesis, mainly in temperate regions. A recent meta-analysis has shown that, in general, the preference-performance hypothesis has been supported, but more data are needed for a proper synthesis on the subject (Gripenberg et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For many herbivorous insects, selection of oviposition site depends on the quality of the host plant for offspring development (Wilson 1988;DiTommaso and Losey 2003;Van Nouhuys et al 2003). As a specialist group of insect herbivores, true fruit flies (Diptera: Tephritidae) are also known to make decisions about which fruit to oviposit into based on the suitability of the fruit for their offsprings' performance (Fitt 1981;Joachim-Bravo et al 2001;Fontellas-Brandalha and Zucoloto 2004).…”
Section: Introductionmentioning
confidence: 99%